2019
DOI: 10.1145/3301415
|View full text |Cite
|
Sign up to set email alerts
|

Non-visual Perception of Lines on a Multimodal Touchscreen Tablet

Abstract: While text-to-speech software has largely made textual information accessible in the digital space, analogous access to graphics still remains an unsolved problem. Because of their portability and ubiquity, several studies have alluded to touchscreens as a potential platform for such access, yet there is still a gap in our understanding of multimodal information transfer in the context of graphics. The current research demonstrates feasibility for following lines, a fundamental graphical concept, via vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We also observed that the number of touches to the corners (edges) was significantly higher (lower) for prototypical square and hexagon than their non-prototypical counterparts. Since humans can perceive horizontal lines more easily than oriented ones (Tennison and Gorlewicz, 2019), perhaps the participants in our experiments recognized the parallel horizontal edges in prototypical square and hexagon easily and focused on the corners more to differentiate them from the others.…”
Section: Haptic Exploratory Procedures For Tactile Shapesmentioning
confidence: 92%
See 2 more Smart Citations
“…We also observed that the number of touches to the corners (edges) was significantly higher (lower) for prototypical square and hexagon than their non-prototypical counterparts. Since humans can perceive horizontal lines more easily than oriented ones (Tennison and Gorlewicz, 2019), perhaps the participants in our experiments recognized the parallel horizontal edges in prototypical square and hexagon easily and focused on the corners more to differentiate them from the others.…”
Section: Haptic Exploratory Procedures For Tactile Shapesmentioning
confidence: 92%
“…They concluded that participants followed non-traditional haptic exploration strategies such as navigating the screen from left to right horizontally and then from top to bottom vertically to recognize the displayed item on the touchscreen. Tennison and Gorlewicz (2019) conducted experiments with visually impaired participants to investigate how they explore virtual line profiles displayed on a touchscreen using auditory and vibratory feedback. Their results suggested that vibrating lines were preferred over auditory lines.…”
Section: Haptic Exploratory Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this limitation, a growing body of work has begun to examine the use of touch/haptic cues as an output modality for applications supporting BVI users. Some notable examples of using touchscreen-based haptics include accessing bar graphs, letter identification, and shape discrimination [6], as well as accessing multi-line data representations [7,8], recognizing shapes and patterns [9,10], and accessing maps [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%